Performance Assessment Through Motion Literation to Assess The Motoric Skill of Junior High School Students Based on Laban Notation - Triana, Dinny Devi; Yudha, Rivo Panji (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
Motor skills integrate physical functions and coordination between the brain as a center for information and control through visual activities (reading) and tactile (writing) movement symbols. Symbols and motion codes are found in labanotation, so the ability to read symbols and write symbol patterns is called motion literacy. It can be done through continuous assessment continuously in an effort to diagnose their abilities. The results of the study describe a change in the condition of students’ motor skills after intervention through labanotation-based motion literacy work assessment, namely the change in conditions from the intervention condition (B) to the final baseline condition (A’) decreases the students’ adaptability. However, at the final baseline condition (A’), the motor ability score improved better than in the phase before baseline (A). The total average score obtained in this condition was 62.86%. Thus it can be concluded that the effect of performance appraisal through motion literacy provides benefits for improving brain function because structured and programmed motion exercises are useful in stimulating various learning centers in the brain. This also impacts on improving motor skills in students to undergo the learning process at a later stage.